Variation in clutch size in relation to nest size in birds. Issue 18 (2nd September 2014) - Møller, Anders P.; Adriaensen, Frank; Artemyev, Alexandr; Bańbura, Jerzy; Barba, Emilio; Biard, Clotilde; Blondel, Jacques; Bouslama, Zihad; Bouvier, Jean‐Charles; Camprodon, Jordi; Cecere, Francesco; Charmantier, Anne; et al.
<x xml:space="preserve">Abstract</x> Clutch size varies consistently with nest size among species of birds, albeit in a species‐specific manner according to 121 slope estimates of the relationship between clutch size and nest size based on 17, 472 clutches. The relationship between clutch size and nest size is causal as shown by three experiments. The reaction norm for clutch size variation with nest size shows an increase at small nest box sizes, but a leveling off at larger nest box sizes. These findings have implications for population studies of hole nesting birds (and other nest‐building animals) because clutch size and hence parental care and reproductive output will in a species‐specific manner depend on the choice of nest box size by scientists. <boxed-text content-type="graphic" id="ece31189-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>